Comprehensive view of a z ∼ 6.5 radio-loud quasi-stellar object: From the radio to the optical/NIR to the X-ray band - Ighina, Luca; Caccianiga, A.; Moretti, A.; Broderick, Jess; Leung, J.K.; Paterson, Sean; Rigamonti, F.; Seymour, Nick; Belladitta, S.; Drouart, G.; Galvin, T.J.; Hurley-Walker, Natasha (2024)
We present a multi-wavelength analysis, from the radio to the X-ray band, of the redshift z=6.44 VIK J2318-31 radio-loud quasi-stellar object, one of the most distant currently known of this class. The work is based on newly obtained observations (uGMRT, ATCA, and Chandra) as well as dedicated archival observations that have not yet been published (GNIRS and X-shooter). Based on the observed X-ray and radio emission, its relativistic jets are likely young and misaligned from our line of sight. Moreover, we can confirm, with simultaneous observations, the presence of a turnover in the radio spectrum at νpeak ∼650 MHz that is unlikely to be associated with self-synchrotron absorption. From the near-infrared spectrum we derived the mass of the central black hole, $ MBH=8.1+6.8-5.6 × 108 M·,and the Eddington ratio, λEDD = 0.8+0.8-0.6, using broad emission lines as well as an accretion disc model fit to the continuum emission. Given the high accretion rate, the presence of a ∼8×108 M· black hole at z=6.44 can be explained by a seed black hole ( ∼104 M·) that formed at z ∼25, assuming a radiative efficiency ηd ∼0.1. However, by assuming ηd ∼0.3, as expected for jetted systems, the mass observed would challenge current theoretical models of black hole formation.